The Contribution of Anti-prothrombin-antibodies to Lupus Anticoagulant Activity - Horbach, Daniëlle A.; Oort, Erica van; Derksen, Ronald H. W. M.; de Groot, Philip G. (Thrombosis and Haemostasis, 1998)
The presence of lupus anticoagulant (LAC) is strongly correlated with a history of thrombosis in patients with SLE. LAC activity can be caused by anti-prothrombin (FII)- and/or anti-β2glycoprotein I (β2GPI)-antibodies.In the present study, the contribution of anti-FII-antibodies to LAC activity was measured in 28 LAC positive plasmas. Plasmas were incubated with prothrombin or BSA, immobilized on CNBr-activated Sepharose, to absorb all anti-FII-antibodies. In 4 out of the 28 plasmas LAC activity was completely dependent on anti-FII-antibodies. In 7 out of the 28 plasmas, anti-FII-antibodies did not contribute to LAC activity. These anti-FII-antibodies can be regarded as non-functional antibodies. In the majority (17/28) of the samples, LAC activity within a single plasma was caused by a combination of antibodies with different specificities. Both dRVVT and KCT showed comparable sensitivity for the detection of functional anti-FII-antibodies.In conclusion, in most samples LAC activity is not caused by anti-FII-antibodies alone but by a combination of different types of antibodies. The presence of LAC activity and anti-FII-antibodies in one plasma does not automatically implicate that these antibodies are responsible for the LAC activity.